The co-occurrence of mental disorders in children and adolescents with intellectual disability/intellectual developmental disorder - Munir, Kerim M. (Curr Opin Psychiatry, 2016)
PURPOSE OF REVIEW: The study summarizes supportive epidemiological data regarding the true co-occurrence (comorbidity) and course of mental disorders in children with intellectual disability/intellectual developmental disorders (ID/IDD) across the lifespan. RECENT FINDINGS: Published studies involving representative populations of children and adolescents with ID/IDD have demonstrated a three to four-fold increase in prevalence of co-occurring mental disorders. The effect of age, sex, and severity (mild, moderate, severe, and profound) and socioeconomic status on prevalence is currently not clearly understood. To date there are no prevalence estimates of co-occurring mental disorders in youth identified using the new DSM-5 (and proposed ICD-11) definition of ID/IDD using measures of intellectual functions and deficits in adaptive functioning with various severity levels defined on the basis of adaptive functioning, and not intellectual quotient scores. SUMMARY: The true relationship between two forms of morbidity remains complex and causal relationships that may be true for one disorder may not apply to another. The new conceptualization of ID/IDD offers a developmentally better informed psychobiological approach that can help distinguish co-occurrence of mental disorders within the neurodevelopmental section with onset during the developmental period as well as the later onset of other mental disorders.